2020
DOI: 10.1097/ta.0000000000002975
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injury induced temperature dysregulation: What is the role of β blockers?

Abstract: BACKGROUND Traumatic brain injury (TBI) is associated with sympathetic discharge that leads to posttraumatic hyperthermia (PTH). Beta blockers (ββ) are known to counteract overactive sympathetic discharge. The aim of our study was to evaluate the effect of ββ on PTH in critically-ill TBI patients. METHODS We performed retrospective cohort analysis of the Medical Information Mart for Intensive Care database. We included all critically ill TBI patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…From 7922 relevant citations, 17 studies met the inclusion criteria (2 prospective, 2 RCTs, and 13 retrospective) 8–12 14 15 17 22–30. A PRISMA flow diagram of the study selection is illustrated in figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From 7922 relevant citations, 17 studies met the inclusion criteria (2 prospective, 2 RCTs, and 13 retrospective) 8–12 14 15 17 22–30. A PRISMA flow diagram of the study selection is illustrated in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies (11 of 17) broadly included all patients who received at least one dose of any beta blocker while in the hospital. Only three studies included information on specific dosing 23 27 29…”
Section: Resultsmentioning
confidence: 99%
“…They also play a role in regulating lipolysis in white adipose tissue, thermogenesis in brown adipose tissue and mobilization of hematopoietic progenitor cells [212]. It has been shown that TBI patients experience sympathetic hyperactivity, causing a catecholamine surge [213][214][215][216][217][218]. This surge causes secondary insults, which manifest as posttraumatic hyperthermia [216,218], increased inflammation and leukocyte migration [219,220], impaired cerebral homeostasis and perfusion [217], and cardiovascular dysfunction [216], and has been associated with increased mortality [221].…”
Section: Beta-blockersmentioning
confidence: 99%
“…ese findings only translated to a shorter ICU stay and lower mortality in the subgroup of patients with head Abbreviated Injury Scale ≥4. [10] A consolidated research effort is being put into the development of effective neuroprotective agents that can improve long-term outcomes after TBI. e discussion of the potential neuroprotective role of beta-blockers merits a short discussion of another promising neuroprotective agent: amantadine.…”
Section: Anti-seizure Prophylaxis and Neuroprotectionmentioning
confidence: 99%
“…These findings only translated to a shorter ICU stay and lower mortality in the subgroup of patients with head Abbreviated Injury Scale ≥4. [ 10 ]…”
Section: Anti-seizure Prophylaxis and Neuroprotectionmentioning
confidence: 99%